Inorganic fertilization effects on the structure of a calcareous silt loam soil - Mooney, Sacha J. (American Society of Agronomy, 2017)
Inorganic fertilizers have been intensely used in the North China Plain (NCP) to maintain or increase crop yields, but their effects on soil physical properties, especially soil structure, are unclear. The objective of this study was to evaluate the effects of 12 years of successive application of inorganic fertilization on soil aggregate stability, pore structure and hydraulic properties of a calcareous silt loam soil. A long-term field experiment (2001 -2013) was established at Luancheng Ecosystem Station, NCP. The experiment included three fertilization treatments:(1) inorganic fertilizer, NPK; (2) inorganic fertilizer and organic manure, NPKOM; and (3) a control treatment with no fertilizer, CK. Results showed plots receiving long-term NPK and NPKOM had significantly greater wheat(275% and 307%, respectively)and maize yields (59% and 107%, respectively) than the control. However, the application of inorganic fertilizer significantly decreased aggregate stability and macroporosity, by 55.3% and 36.1%, respectively, relative to the control. No differences in soil organic carbon (SOC), bulk density (BD), saturated conductivity (Ks), and water-holding capacity were found between the NPK and the CK treatments. On the other hand, the addition of organic manure with inorganic fertilizers increased SOC, total porosity, and saturated conductivity by 38.5%, 5.2%, and 75%, respectively compared to the CK treatment. This study indicated inorganic fertilization alone could not improve soil structure of the calcareous silt loam, although it maintained high yields. Use of organic amendments along with inorganic fertilizers can improve soil structure and crop yields.